Defending the digital frontier : practical security for management - Babiak, Jan. (Wiley, 2005)
Enhance the digital security knowledge-base within any organization. In today's competitive business environment, information and information technology have become crucial for a company's success. Ensuring the confidentiality of such information-financial, trade secrets, and the like-has become key. Defending the Digital Frontier, Second Edition describes where organizations are vulnerable and identifies protective measures that rely on people and process as much as technology. This book is a practical guide aimed at business leaders and executives, explaining why digital security is not a technical function, but a risk management operation, and illustrates an approach for creating an enterprise-wide security culture based on business-led risk-management principles. Ernst & Young is a global leader in professional services, providing tax, assurance, and transaction advice to thousands of individuals as well as domestic and global businesses. Ernst & Young provides independent security solutions for some of the world's most information-intensive organizations, including numerous Fortune 500 companies, and the federal government.